National problem and class struggle in the War of the Pacific: The resistance of La Breña in the Sierra Central, 1881-1886 - Mallón, Florencia E. (1981)
The recent centenary of the beginning of the War of the Pacific (1879-1884) has generated an intense debate on the national problem and the development of nationalist consciousness in Peru. Faced with the rapid defeat suffered by the Peruvian army (1879-1881) and the disunity of the population during the Chilean occupation (1881-1884), historians have begun to wonder if the various sectors of Peruvian society knew how to ignore their ethnic, racial or class interests to give priority to the fight against the invader. One position in this debate, forming part of the new historiographical trend that criticizes the most sterilely patriotic assumptions of nineteenth-century Peruvian history, maintains that the population in general, instead of uniting in the common defense of the national territory, preferred to remain neutral. or even ally with the Chileans against their internal enemies.